The Relationship Between Alexithymia and Type 2 Diabetes: A Systematic Review - Martino, Gabriella; Caputo, Andrea; Vicario, Carmelo M.; Catalano, Antonino; Schwarz, Peter; Quattropani, Maria C. (Frontiers in Psychology, 2020)
Background: This systematic review analyzed the relationship between alexithymia, considered as the inability to recognize and express thoughts and emotions, and type 2 diabetes mellitus (T2DM), one of the most common chronic illness, which is characterized by a metabolic disorder burdened by high morbidity and mortality worldwide due to its outcomes. Methods: PRISMA guidelines were followed throughout this systematic review of the recent literature indexed in the databases PubMed, PsycInfo, Scopus and Web of Science. Search terms for eligible studies were: “Type 2 diabetes” OR “T2DM” AND “Toronto Alexithymia Scale” OR “TAS-20”[All Fields]. Results: The initial search identified 61 indexed scientific publications. After screening we found that 7 publications met the established scientific inclusion and exclusion criteria. It emerged that alexithymic patients ranged from 25% to 50% across the examined publications and it appeared that patients with T2DM generally reflected greater values of alexithymia, revealing particular differences among TAS domains. Moreover, emlpoyed participants were alexithymic to a greater extent compared to non-working participants (77.8% vs 35.4%) and alexithymia was 2.63 times more severe among working participants when examining predictors of alexithymia. When evaluating the correlations between alexithymia and HbA1c or fasting blood glucose levels we found strong associations equal to 0.75 and 0.77 for TAS-20 total scores, respectively. While alexithymic participants showed significantly higher levels of HbA1c and blood glucose when compared to the non-alexithymic participants. Conclusions: The results of this systematic review of the current literature highlight the need of alexithymia evaluation in patients with T2DM. The high prevalence in T2DM and strong associations with poorly regulated diabetes and psychological distress, indicate a significant relationship between poor glycemic control and psychological distress, such as anxiety and depression, and quality of life. Further studies are needed focusing on age and gender differences in order to be able to improve clinical psychological care and prevention.